Paradigma Dan Rasionalitas: Telaah Kritis Pemikiran Thomas Kuhn Dan Ibnu Rusyd - Al Hafied, L. Ibnurusd; Nurmayanti, Eka (Kartika: Jurnal Studi Keislaman, 2025)
This article aims to analyze and compare Thomas Kuhn’s concept of scientific paradigms with Ibn Rushd’s philosophical notion of rationality, while exploring their relevance to the development of contemporary epistemology. The study departs from the assumption that the tension between scientific relativism and objective rationalism lies at the core of methodological problems in modern philosophy of science. Employing a comparative-philosophical approach with textual analysis, this research examines primary sources such as Kuhn’s The Structure of Scientific Revolutions and Ibn Rushd’s Tahafut al-Tahafut and Faṣl al-Maqal supplemented by secondary literature from contemporary scholars. The findings reveal that Kuhn views scientific progress as a revolutionary process shaped by paradigm shifts and scientific community consensus, whereas Ibn Rushd emphasizes universal rationality grounded in the harmony between reason and revelation. Both thinkers share a critical stance against intellectual dogmatism and advocate for the emancipation of reason from oppressive authority. The synthesis of their ideas provides a philosophical foundation for reinforcing scientific rationality based on ethical values, while offering an integrative and contextual framework for reconstructing modern epistemology.